STF’S 1.069 THEME IN LIGHT OF THE CONCEPTS OF COMPETENCE AND PROGRESSIVE AUTONOMY OF CHILDREN AND ADOLESCENTS (Reflection and Critique Law Magazine, 2025)
As currently provided in Brazilian civil legislation, children and adolescents are deemed to have relative or absolute legal incapacity, depending on their age. Such incapacity, although established by law, has its foundations on the quality of discerniment. This rigid and inflexible limitation has led both doctrine and jurisprudence on a search for a form of balance between protection and autonomy of minors, particularly in matters involving existential choices. It is certain that those choices cannot be peremptorily denied to children and adolescents, at the risk of limiting their free development of the personality. Therefore, the analysis of Theme 1.069 emerges as being of singular importance, a case of general repercussion ruled by Brazil’s Supreme Court, according to which Jehovah's Witness minors ought not to have their will taken into consideration in cases of refusal of blood transfusion. The concepts of “progressive autonomy” and “competence” are introduced with the goal of clarifying that a minor can show the necessary discernment that is required for the validation of a specific act, such as a medical choice. This demonstration leads to the conclusion that the concept of civil incapacity can be deconstructed in cases that its premise (e.g. the discernment) is verified in practice.